High genetic diversity of paramyxoviruses infecting domestic cats in Western Brazil - Darold, Gabriela Molinari; Alfieri, Amauri Alcindo; Araújo, João Pessoa [UNESP]; da Cruz, Taís Fukuta [UNESP]; Bertti, Káryta Maria de Lima Bezerra; da Silva, Glaucenyra Cecília Pinheiro; Amude, Alexandre Mendes; Muraro, Lívia Saab; Lavorente, Fernanda Louise Pereira; Lunardi, Michele (Hindawi, 2020)
Feline morbillivirus was discovered in 2012 in cats from Hong Kong, and it was initially found to be associated with chronic kidney disease. Although subsequent molecular surveys showed a common occurrence in cat populations from distinct countries, there were controversial results regarding the relationship between viral shedding through urine and reduced kidney function. In this study, 276 domestic cats of diverse origins from Western Brazil had their urine evaluated for the presence of paramyxoviral RNA by reverse transcription seminested PCR and direct sequencing. Additionally, a selected Brazilian feline morbillivirus strain was isolated in Crandell Rees feline kidney cells, and a nearly complete genome sequence was obtained. To assess the kidney function of all cats, serum biochemistry screening and standard urinalysis were performed. Our results revealed a relatively high paramyxovirus-positive rate (34.7%) in the evaluated cats although there was not a statistical association between the shedding of viral RNA through urine and kidney disease. Direct sequencing of partial fragments of the L gene demonstrated high genetic diversity among strains detected in cats in this study, since both feline morbillivirus RNA and feline paramyxovirus RNA were frequently shed in urine. Phylogenetic reconstruction based on partial amino acid sequences of the L gene showed that Brazilian feline paramyxovirus strains were genetically diverse since they grouped into two distinct subclusters; one subcluster contained three strains identified in Germany, while the second contained Japanese strain 163, which was recently classified in the Jeilongvirus genus of the Paramyxoviridae family. In contrast, the Brazilian feline morbillivirus strain FeMV/BR_Boni, herein characterized by nearly complete genome sequencing, was classified in the Morbillivirus genus with other strains previously identified as genotype 1. In conclusion, urinary excretion of diverse paramyxoviral RNA is frequent in cats of different origins from Western Brazil, but viral infection is not related to altered kidney function.
Keywords: chronic kidney disease; FeMV; FPaV; morbillivirus; PCR; South America